Performance management in parastatals: the cases of the Zimbabwe United Passenger Company and the National Railways of Zimbabwe - Matunhu, Jephias; Matunhu, Viola (Africa Institute of South Africa, 2016)
The Zimbabwe United Passenger Company (ZUPCO) and the Zimbabwe National Railways (NRZ) are parastatals operating in the transport industry. Both organisations suffered a setback due to the economic structural adjustment programmes imposed by the International Monetary Fund (IMF), hyperinfl ation, the current brain drain and the effects of the liberalisation of the transport sector in Zimbabwe. In a bid to recover from this crunch, both organisations instituted performance management systems, which were borrowed from the public sector. Now the question is, “have these performance management systems improved the effectiveness of parastatals in Zimbabwe?”